2014
DOI: 10.1038/jcbfm.2014.103
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Neurovascular Function and Functional Recovery after Stroke in the Rat Striatum Using Forepaw Stimulation

Abstract: Negative functional magnetic resonance imaging (fMRI) response in the striatum has been observed in several studies during peripheral sensory stimulation, but its relationship between local field potential (LFP) remains to be elucidated. We performed cerebral blood volume (CBV) fMRI and LFP recordings in normal rats during graded noxious forepaw stimulation at nine stimulus pulse widths. Albeit high LFP-CBV correlation was found in the ipsilateral and contralateral sensory cortices (r ¼ 0.89 and 0.95, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 48 publications
1
25
1
Order By: Relevance
“…Although it may be intuitive to interpret our data as DBS-evoked neuronal inhibition, the situation appears to be particularly muddled in striatum, wherein dopaminergic neurotransmission has been hypothesized to induce vasoconstriction independent of direct activity changes within striatal neurons (Hsu et al, 2014) or regional metabolism (Shih et al, 2011). In addition, striatal CBV decreases have previously been shown with heightened local neuronal activity, as observed in rats during noxious forepaw stimulation (Shih et al, 2009; Shih et al, 2014a), or epileptic slow-wave discharge (Mishra et al, 2011). In light of these complexities, further work will be necessary to determine the underlying mechanism of striatal CBV decreases evoked during GPe- and SNr-DBS.…”
Section: Discussionmentioning
confidence: 83%
“…Although it may be intuitive to interpret our data as DBS-evoked neuronal inhibition, the situation appears to be particularly muddled in striatum, wherein dopaminergic neurotransmission has been hypothesized to induce vasoconstriction independent of direct activity changes within striatal neurons (Hsu et al, 2014) or regional metabolism (Shih et al, 2011). In addition, striatal CBV decreases have previously been shown with heightened local neuronal activity, as observed in rats during noxious forepaw stimulation (Shih et al, 2009; Shih et al, 2014a), or epileptic slow-wave discharge (Mishra et al, 2011). In light of these complexities, further work will be necessary to determine the underlying mechanism of striatal CBV decreases evoked during GPe- and SNr-DBS.…”
Section: Discussionmentioning
confidence: 83%
“…25 Images were skull-stripped, co-registered across subjects and analyzed using established protocols that we published previously. 26, 27 Specifically, CBF was calculated from CSL data using CBF=false(λ/T1false)false(SC-SLfalse)false(SL+false(2α-1false)SCfalse), where S C and S L are the MR signal intensities from the control and labeled images, respectively. λ is the water brain-blood partition coefficient, T 1 is that of tissue, and α is the arterial spin-labeling efficiency.…”
Section: Methodsmentioning
confidence: 99%
“…The changes of neurovascular coupling also dynamically occur after focal cerebral ischemia and during recovery. Monitoring neurovascular coupling through cerebral blood volume fMRI and local field potential (LFP) after forepaw stimulation, Shih and coworkers (Shih et al, 2014) reported that both the fMRI and LFP responses in the cortex and striatum of the affected hemisphere were diminished immediately after stroke and recovered on day 28 after experimental stroke. In agreement with the experimental findings, an fMRI study in chronic stroke patients has revealed that an increase of regional cerebral blood flow is positively correlated to a significant recovery in speech and limb motor function (Mountz, 2007).…”
Section: The Intrinsic Capability Of Brain Self-repair In Stroke Recomentioning
confidence: 99%